α-1 Antitrypsin Inhibits RANKL-induced Osteoclast Formation and Functions - Mohammad Ahsanul Akbar; David Nardo; Mong-Jen Chen; Ahmed S. Elshikha; Rubina Ahamed; Eslam M. Elsayed; Claire Bigot; L. Shannon Holliday; Sihong Song (BMC, 2017)
Abstract Osteoporosis is a global public health problem affecting more than 200 million people worldwide. We previously showed that treatment with α-1 antitrypsin (AAT), a multifunctional protein with antiinflammatory properties, mitigated bone loss in an ovariectomized mouse model. However, the underlying mechanisms of the protective effect of AAT on bone tissue are largely unknown. In this study, we investigated the effect of AAT on osteoclast formation and function in vitro. Our results showed that AAT dose-dependently inhibited the formation of receptor activator of nuclear factor κB ligand (RANKL)-induced osteoclasts derived from mouse bone marrow macrophage/monocyte (BMM) lineage cells and the RAW 264.7 murine macrophage cell line. To elucidate the possible mechanisms underlying this inhibition, we tested the effect of AAT on the gene expression of cell surface molecules, transcription factors and cytokines associated with osteoclast formation. We showed that AAT inhibited macrophage colony-stimulating factor (M-CSF)-induced cell surface RANK expression in osteoclast precursor cells. In addition, AAT inhibited RANKL-induced TNF-α production, cell surface CD9 expression and dendritic cell-specific transmembrane protein (DC-STAMP) gene expression. Importantly, AAT treatment significantly inhibited osteoclast-associated mineral resorption. Together, these results uncover new mechanisms for the protective effects of AAT and strongly support the notion that AAT has therapeutic potential for the treatment of osteoporosis.